STAD Learning Model and Learning Styles: Learning Outcomes of Fifth-Grade Students at Primary School - Jela A. Rahawarin; Samuel P. Ritiauw; Leonid Ritiauw (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Use of less diverse learning models and neglect of students' learning styles can lead to inferior social studies learning outcomes in elementary school children and a lack of classroom participation. This study examines how the Student Teams Achievement Division (STAD) learning model and learning styles affect fifth-grade social studies learning results in Primary School 2 Latihan Ambon. This experiment used a 2x3 factorial analysis and a posttest-only control group. All Primary School 2 Latihan Ambon pupils were studied, with 42 students divided into an experimental class (22 students) using the STAD model and a control class (20 students) using the TGT model, which stands for Teams Games Tournament, another cooperative learning model. A validated learning style questionnaire and learning outcome test were employed. Data was evaluated with a two-way ANOVA. The research findings showed that: (1) The STAD learning model had a significant effect on student learning outcomes (Sig. 0.000 < 0.05), with the average score of the experimental class (81.667) higher than the control class (63.267). (2) Learning styles have a significant influence on learning outcomes (Sig. 0.000 < 0.05), where students with visual learning styles achieved the highest score (84.400), followed by kinesthetic (69.800) and auditory (63.200). (3) There is a significant interaction between learning models and learning styles on student learning outcomes (Sig. 0.002 < 0.05). This study helps educators map student learning styles before choosing a model. These findings also support the STAD cooperative model's ability to boost primary school social studies material achievement.